Effect of the Resin-Based Adhesive Coating on the Shear Punch Strength of Aesthetic Restorative Materials - Najmeh Mohammadi; Rafat Bagheri; Lida Vaziri Borazjani (Wolters Kluwer Medknow Publications, 2021)
Introduction: This study aimed to investigate the effect of G-Coat Plus (GCP) on the shear punch strength (SPS) of conventional glass ionomer cements (CGICs) and resin composites (RCs). Materials and methods: In this experimental study, four groups of restorative materials (two CGICs (Equia Forte Fil and Fuji Bulk), and two RCs (Aura Bulk fil and Filtek Z250) were used. Twenty specimens were prepared for each material. GCP was applied on the first subgroup (n = 10). The specimens were stored in distilled water at 37°C, and SPS values were measured after 24 hours. Two-way analysis of variance and independent t test were used for data analysis. Results: RCs showed significant higher SPS values compared to the CGICs (P < 0.001). All materials tested showed increased SPS values after applying GCP (P < 0.05). Conclusion: Applying GCP significantly improves the SPS of tooth-colored restorative materials used in this study.